Control of indigenous quorum quenching bacteria on membrane biofouling in a short-period MBR. (July 2019) - Huang, Jinhui; Gu, Yanling; Zeng, Guangming; Yang, Ying; Ouyang, Yichen; Shi, Lixiu; Shi, Yahui; Yi, Kaixin
Graphical abstract: Highlights: An indigenous QQ bacteria is efficient on biofouling control in the short-period MBR. The QQ bacteria has an inhibiting effect on EPS and SMP in MBR mixed liquor. EPS and SMP contents are linearly dependent on AHLs concentration in mixed liquor. QQ bacteria has an effect on the variation of TMP at different stages. Abstract: In this paper, the immobilized quorum quenching (QQ) bacteria – microbial bag was added to a short-period membrane bioreactor (MBR) and its antifouling ability and mechanism were studied by monitoring the changes in transmembrane pressure (TMP), along with the production of N-acyl-homoserine lactones (AHLs), extracellular polymeric substance (EPS) and soluble microbial products (SMP). The QQ bacteria showed efficient mitigation of TMP increase in different membrane fouling stages. In the control MBR group, the TMP reached 43 kPa on the 4th day, while in the experimental group, TMP of QQ-MBR was only 18 kPa at the same time. The detection result of EPS and SMP content of protein and polysaccharide in MBRs showed that QQ bacteria had significant inhibitory effects on EPS and SMP. Also, the QQ bacterial exhibited excellent AHLs degradation rate in MBR reaction tank.